An ESCRT module is required for neuron pruning. - Loncle, N.; Agromayor, M.; Martin-Serrano, J.; Williams, D.W. (Scientific reports, 2015)
Neural circuits are refined by both functional and structural changes. Structural remodeling by large-scale pruning occurs where relatively long neuronal branches are cut away from their parent neuron and removed by local degeneration. Until now, the molecular mechanisms executing such branch severing events have remained poorly understood. Here, we reveal a role for the Endosomal Sorting Complex Required for Transport (ESCRT) machinery during neuronal remodeling. Our data show that a specific ESCRT pruning module, including members of the ESCRT-I and ESCRT-III complexes, but not ESCRT-0 or ESCRT-II, are required for the neurite scission event during pruning. Furthermore we show that this ESCRT module requires a direct, in vivo, interaction between Shrub/CHMP4B and the accessory protein Myopic/HD-PTP.